Organizational and legal framework for the strategic development of commercial banks - Ibrokhimova Nazokat (THE INNOVATION ECONOMY, 2026)
This article examines the organizational and legal foundations of the strategic development of commercial banks. In the context of the development of the digital economy, state support for the further development of the activities of commercial banks, the introduction of advanced foreign experience into practice, and the main directions of strategic transformation are analyzed.